Factors Affecting Nurse Performance at Service Technical Implementation Unit Teluk Dalam Public Health Center, South Nias Regency - Hesron Ariamito Ginting; Ismail Efendy; Nur’aini Nur’aini (Newinera Publisher, 2022)
Motivation is the driving force for nurses to try to achieve maximum work performance in accordance with the work targets achieved. This study aims to analyze the factors that influence the performance of nurses in the UPTD of Teluk Dalam Public Health Center, South Nias Regency. This research was a quantitative study with a research design using the Analytical Survey method with a Cross Sectional approach. The research was conducted at the UPTD of the Teluk Dalam Public Health Center, South Nias Regency, from July to August of 202. The number of samples was 70 nurses who were obtained by total sampling. The data in this study include primary data, secondary data and tertiary data. Data analysis was performed using univariate analysis test, bivariate analysis using Chi-square test and multivariate using logistic regression test. The results showed that that there is an effect of responsibility, recognition of work results, incentives, work procedures, opportunities to continue education on the performance of nurses in the UPTD of Teluk Dalam Public Health Center, South Nias Regency. The results of multivariate analysis show that the most dominant variable influencing is the responsibility variable. Based on the results of this study, it is recommended that the results of this study become input for the management of the Teluk Dalam Public Health Center in South Nias Regency, to carry out continuous guidance to all nurses so that they are able to be responsible for every task assigned by the leadership.